Efektivitas Metode Diskusi Kelompok dalam Meningkatkan Pemahaman Nilai Sosial pada Kelas IV SD - Hamna; Putri Syawalia; Ade Novita; Reski Amalia (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
This research examines the implementation of the group discussion method in Social Studies learning to enhance the understanding of social values among 4th-grade elementary school students. The research employed a qualitative approach, collecting data through classroom observations, in-depth interviews with teachers and students, and document analysis. The findings reveal that the group discussion method positively impacts students' social values when implemented with proper preparation, balanced group formation, and effective teacher facilitation. The method promotes active participation, collaborative learning, and social skill development. However, challenges were identified, including participation inequality, time management issues, and the need for teachers' guidance throughout the process. This research contributes to understanding effective teaching strategies for social values education in elementary settings and offers practical recommendations for educators implementing discussion-based learning approaches.